2021
DOI: 10.1177/14773708211035301
|View full text |Cite
|
Sign up to set email alerts
|

Examining experiential fear of crime using STUNDA: Findings from a smartphone-based experience methods study

Abstract: Situational data have become more frequently used in research on offending and victimization. However, one outcome that has received less attention is fear of crime. The current study uses situational data collected through a smartphone application (STUNDA) to examine fear of crime as it is experienced in daily life among a sample of university students. Roughly 1200 situations reported by 129 students were analysed using generalized estimating equations. The results indicate that experiential fear of crime, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…Future research may wish to consider using an item that asks participants whether they believe that they will fall victim to crime in their current location to avoid manipulating spatial distance while retaining the egocentric point of reference. This is also in line with previous fear of crime research, which asks participants to estimate their risk of becoming a victim of crime in their immediate environment (Chataway et al, 2017; Chataway & Mellberg, 2021; Engström & Kronkvist, 2021; Irvin-Erickson et al, 2020; Solymosi et al, 2015).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Future research may wish to consider using an item that asks participants whether they believe that they will fall victim to crime in their current location to avoid manipulating spatial distance while retaining the egocentric point of reference. This is also in line with previous fear of crime research, which asks participants to estimate their risk of becoming a victim of crime in their immediate environment (Chataway et al, 2017; Chataway & Mellberg, 2021; Engström & Kronkvist, 2021; Irvin-Erickson et al, 2020; Solymosi et al, 2015).…”
Section: Discussionsupporting
confidence: 75%
“…It is unclear why this is the case, given previous fear of crime research has identified the importance of perceptions of space and place for influencing individual's worry about crime and risk perception (Chataway & Mellberg, 2021;Irvin-Erickson et al, 2020;Solymosi et al, 2015). Scholars such as Chataway et al, (2017) and Engström and Kronkvist (2021) have used surveys delivered via smartphones to ask participants about their level of worry about and perceived risk of becoming a victim of crime in their current location. By asking participants to respond to questions about their perceived risk of becoming a victim of crime in their immediate environment, Chataway et al, (2017) and others have found that individuals' perceptions of their immediate environment are ecologically valid predictors of their worry about crime (Engström & Kronkvist, 2021;Irvin-Erickson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a convenience sample of roughly 200 students, the project has proven two main points. First, fear of crime varies across different contexts in our daily lives, suggesting that fear appears to be a fairly dynamic phenomenon (Engström & Kronkvist, 2021). Second, it is both possible and feasible to employ alternative methodological approaches to study this dynamic form of fear of crime (Kronkvist & Engström, 2020).…”
Section: Introductionmentioning
confidence: 99%